2018
DOI: 10.1007/5584_2018_220
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue-Derived Stromal Cells for Wound Healing

Abstract: Skin as the outer layer covers the body. Wounds can affect this vital organ negatively and disrupt its functions. Wound healing as a biological process is initiated immediately after an injury. This process consists of three stages: inflammation, proliferation, remodeling. Generally, these three stages occur continuously and timely. However, some factors such as infection, obesity and diabetes mellitus can interfere with these stages and impede the normal healing process which results in chronic wounds. Financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 153 publications
0
36
0
Order By: Relevance
“…Furthermore, a previous study has reported that HMSCs-CM also have a ability to induce chemotaxis and angiogenesis regarding accelerated tissue regeneration (Quade, et al, 2020). The VEGF is one of the most important proangiogenic mediators in addition fibroblast proliferation associated with collagen synthesis that is an essential to induce wound healing at any stage of healing process (Goodarzi, et al, 2018;Johnson & Wilgus, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study has reported that HMSCs-CM also have a ability to induce chemotaxis and angiogenesis regarding accelerated tissue regeneration (Quade, et al, 2020). The VEGF is one of the most important proangiogenic mediators in addition fibroblast proliferation associated with collagen synthesis that is an essential to induce wound healing at any stage of healing process (Goodarzi, et al, 2018;Johnson & Wilgus, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the great discoveries have highlighted that MSCs as regenerative medicine soldiers have long been regarding, based on their multi-potential differentiation capacity and self-renewal ability along with immunomodulatory potency. (Fitzsimmons et al 2018;Goodarzi et al 2018a, b). For instance, some investigations were shown that there is a higher survival rate in the subjects with H7N9 influenza who received MSC therapies compared to control group (Singh et al 2020).…”
Section: Importance Of Cell Therapy and Regenerative Medicinementioning
confidence: 99%
“…bone marrow (BM), adipose tissue (AT), placenta (PL), umbilical cord (UC), etc.) and have high-efficiency expansion potential can be effective through their limitless selfrenewal and multi-potential differentiation ability along with their paracrine mediators' association (Aghayan et al 2014;Heo et al 2016;Goodarzi et al 2018a, b;Leng et al 2020). Hereupon, this review focuses on the auxiliary role of MSCs to reduce inflammatory processes of severe ARIs in Cases.…”
mentioning
confidence: 99%
“…The multipotent feature of cSVF can stimulate the production of, and terminally differentiate into cells of the existing niche; moreover, their secretome is enriched with an array of soluble factors that have the capacity to promote neoangiogenesis, cytoprotection, or activation of reparative mechanisms . Clinically, autologous cSVF has been used for many different clinical indications such as to regenerate and repair bone and cartilage in concert with bone grafting , in the treatment of osteoarthritis , and in the management of peripheral vascular disease sequela such as chronic wounds . Cellular SVF has been very effective in the treatment of perianal and recto vaginal fistulas as well as for Crohn's disease , in the treatment for the sequela of radiation injury such as fibrosis, atrophy, retraction, and soft tissue ulceration and to reduce aberrant scar formation .…”
Section: Liposuction Aspirate Fluid (Infranatant) Processingmentioning
confidence: 99%